STUDY ON THE AMINO ACID COMPOSITION OF CRUDE FICIN ENZYME FROM Ficus padana Burm.f. USING SOLAR DRYING - Ismed, Ismed; Yenrina, Rina; Hasbullah, Hasbullah; Syukri, Daimon; Yusniwati, Yusniwati (Institute of Computer Science (IOCS), 2024)
Ficin is an enzyme derived from Ficus sp., recognized for its applications in the food and pharmaceutical sectors. Utilizing solar energy for enzyme drying has been shown to be economical and environmentally sustainable while preserving enzyme activity. This study aimed to determine the amino acid composition of crude ficin from Ficus padana Burm. f., and was extracted and dried with solar energy. The analysis of amino acid components was conducted using the UPLC technique. The results indicated the presence of numerous important amino acids, with L-aspartic acid being the highest concentrated at 1.85 mg/g and L-leucine at 1.41 mg/g. Significant quantities of L-glutamic acid (1.33 mg/g), L-serine (1.14 mg/g), and L-lysine (1.05 mg/g) were also identified. The solar drying process showed no significant loss of amino acids. The findings suggest that solar drying does not negatively impact the amino acid composition in fiction, therefore enhancing its practical significance, particularly for the food and pharmaceutical sectors.